IMPLEMENTASI PEMBELAJARAN BAHASA INDONESIA BERBASIS TEKS DI SMPN 1 BAMBANGLIPURO BANTUL - Himawan, Riswanda (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2022)
21st century learning, including Indonesian language learning requires students to think critically and creatively. The ministry’s policy regarding text-based Indonesian language teaching shows that learning Indonesian language today is not only about memorizing but also creating. In line with this, this study aims to describe the results of the implementation of text-based Indonesian language teaching at SMPN 1 Bambanglipuro Bantul and to describe student responses regarding the implementation of the policy. This study uses a descriptive method with a qualitative approach. Data used in answering research questions are the results of observations and interviews, as well as analysis of documents related to lesson plans made and applied by teachers in teaching Indonesian language to students at SMPN 1 Bambanglipuro. The results show that the teacher as a learning facilitator was able to design lesson plans in accordance with the text-based Indonesian language learning curriculum, which prioritized the process and created outcomes. Students feel happy because in textbased Indonesian language learning, students are encouraged to enjoy reading. This is an excellent policy, because it is important to make reading a daily habit, especially to improve students’ literacy skills.